Clinical assessment of bone quality at implant site using CBCT and hounsfield unit - Nidhi Singh; Subhash Sonkesriya; Shivanand B Bagewadi; Sana Anwar; Sajith Abraham; Anuj Singh Parihar; Azhar Mohammed (Wolters Kluwer Medknow Publications, 2023)
Objectives: The current research was done to assess the bone quality at implant site using CBCT. Materials and Methods: The present study was conducted on 50 partially edentulous patients of both genders. All subjects had their chests scanned using a Kodac machine set to 120 kVp, 12 mA, and a 17-second exposure time. Using Hounsfield units, bone quality was classified as D1, D2, D3, D4, and D5 (HU). Result: Out of 50 patients, 27 were males and 23 were females. The average HU was 786.1 at the anterior maxilla, 1174.3 at the anterior mandible, 332.1 at the posterior maxilla, and 742.4 at the posterior mandible. The variation was considerable (P-0.01). Conclusion: The anterior mandible, anterior maxilla, posterior mandible, and posterior maxilla were found to have the highest densities. Based on Hounsfield units, CBCT is helpful in determining the bone density at the implant site.